Evaluation of teacher development programmes : perspectives on professional learning communities in Siyabuswa Circuit-Mpumalanga Province - Tshehla, Hlanyana Andries (My University, 2022)
The effective delivery of quality education depends, to a greater extent, on the quality of teachers. These teachers need to keep pace with the continuous growth of professional knowledge, skills and competences. This study evaluates teacher development programmes in Siyabuswa Circuit, Mpumalanga Province. Professional Learning Communities (PLC) is one of the initiatives that support and improve teacher knowledge and competences. Hence this study seeks to obtain teachers’ perspectives of the PLCs as a teacher development programme. This will probably shed more light into challenges faced by teachers in participating and benefitting from these developmental programmes. Scharmer (2009) states that when a new development unfolds, people may respond to it in two ways: they muddle through or fight back. Scharmer’s Theory U is thus reflected upon in this study as well to help explain and clarify these perspectives so that appropriate strategies can be found to improve teacher development and quality performance in turn.
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2022
Keywords: Programme evaluation; Teacher professional development; Professional Learning Communities; Theory U; Integrated Strategic Planning Framework for Teacher Education and Development; Professional learning communities; Teachers; Education; Total quality management in education; Teachers -- In-service training